До проблеми інженерно-будівельної оцінки територій з урахуванням локальних природних і техногенних факторів (на прикладі Ренійського р-ну Одеської обл.) - Жирнов, П.В. (Геофизический журнал, 2015)
Рассмотрена проблема влияния локальных природных и техногенных факторов на изменение инженерно-геологических условий строительных участков на примере Ренийского р-на Одесской обл. Проведен анализ геоморфологических, тектонических, литологических, гидрогеологических, геодинамических факторов в пределах Ренийского р-на, что позволило отнести строительные участки к категории сложных по инженерно-геологическим условиям. С учетом данных факторов более точно и качественно выполнено инженерно-геологическое районирование исследуемого региона и выделены особо опасные участки для строительного освоения. This article is devoted to the problem of influence of local natural and technogenic factors on the engineering geological conditions change of building sites, the Reni district of Odessa region as an example. In the article the analysis of geomorphological, tectonic, lithological, hydrogeological, geodynamic factors in the limits of Reni district has been done that determines the definition of building sites as ones of the complicated category by engineering geological conditions . Taking these factors into account helps to carry out more precisely and qualitatively engineering geological zoning of research area and to allocate especially dangerous sites for construction development.